Contribution by vertebrates to seed dispersal effectiveness in the Galápagos Islands: a community-wide approach - Nogales, M. (2017)
Seed dispersal and seedling recruitment are crucial phases in the life cycle of all spermatophyte plants. The net contribution of seed dispersers to plant establishment is known as seed dispersal effectiveness (SDE) and is defined as the product of a quantitative (number of seeds dispersed) and a qualitative (probability of recruitment) component. In Galápagos, we studied the direct contribution to SDE (number of seeds dispersed and effect on seedling emergence) provided by the five island groups of frugivores (giant tortoises, lizards, medium-sized passerine birds, small non-finch passerine birds, and finches) in the two main habitats in this archipelago: the lowland and the highland zones, and found 16 vertebrate species dispersing 58 plant species. Data on frequency of occurrence of seeds in droppings and number of seeds dispersed per unit area produced contrasting patterns of seed dispersal. Based on the former, giant tortoises and medium-sized passerines were the most important seed dispersers. However, based on the latter, small non-finch passerines were the most important dispersers, followed by finches and medium-sized passerines. The effect of disperser gut passage on seedling emergence varied greatly depending on both the disperser and the plant species. Although the contribution to SDE provided by different disperser guilds changed across plant species, medium-sized passerines (e.g., mockingbirds) provided a higher contribution to SDE than lava lizards in 10 out of 16 plant species analysed, whereas lava lizards provided a higher contribution to SDE than birds in five plant species. While both the quantitative and qualitative components addressed are important, our data suggests that the former is a better predictor of SDE in the Galápagos archipelago.